2021
DOI: 10.1073/pnas.2018627118
|View full text |Cite
|
Sign up to set email alerts
|

Modular complement assemblies for mitigating inflammatory conditions

Abstract: Complement protein C3dg, a key linkage between innate and adaptive immunity, is capable of stimulating both humoral and cell-mediated immune responses, leading to considerable interest in its use as a molecular adjuvant. However, the potential of C3dg as an adjuvant is limited without ways of controllably assembling multiple copies of it into vaccine platforms. Here, we report a strategy to assemble C3dg into supramolecular nanofibers with excellent compositional control, using β-tail fusion tags. These assemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…We previously demonstrated that a peptide termed β tail can slowly transition from an α helix to a β sheet conformation and coassemble with Q11 nanofibers even when conjugated to a folded protein ( 28 , 35 ). With such property, β tail serves as a versatile tool for incorporating folded protein antigens in nanofibers formed by self-assembling β sheet peptides.…”
Section: Resultsmentioning
confidence: 99%
“…We previously demonstrated that a peptide termed β tail can slowly transition from an α helix to a β sheet conformation and coassemble with Q11 nanofibers even when conjugated to a folded protein ( 28 , 35 ). With such property, β tail serves as a versatile tool for incorporating folded protein antigens in nanofibers formed by self-assembling β sheet peptides.…”
Section: Resultsmentioning
confidence: 99%
“…Utilizing the adjuvanting effect of the complement protein, C3dg, Hainline et al designed an anti-TNF vaccine formed by Q11 nanofibers co-assembled with C3dg bearing a beta-tail handle (βtail-C3dg). 199,200 C3dg Fig. 4 Overview of current strategies to integrate T cell help for B cell immunity.…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%
“…[ 100 ] Aside from oncoantigens, Q11 has been used for a wide variety of antigens including viral antigens such as HIV gp120 envelope glycoprotein [ 101,102 ] and self-antigens such as anti-TNF B cell epitopes. [ 103,104 ] When antigens were used in conjunction with T cell epitopes and adjuvants, such as STING and TLR9 agonists [ 105 ] or complement protein C3dg 104 , enhanced immunogenicity was seen in immunized mice. Q11 has been shown to be a versatile platform to display various antigens for different vaccine applications.…”
Section: Genetic Fusion Of Recombinant Antigens To Natural Self-assem...mentioning
confidence: 99%